E-governance in the public sector : a case study of the central admission system in Tanzania - Mahundu, Fabian G (Rhodes University, Faculty of Humanities, Department of Sociology, 2016)
This thesis sets out to answer the following central research question: what are the influences, challenges, benefits and costs of the Central Admission System (CAS) as an e-Governance initiative in improving undergraduates' admissions service delivery and quality assurance in Tanzania's higher education institutions?' In answering this key question, three sub-questions were explored: (1) To what extent and in what ways does the implementation of the CAS influence the organisation of admissions work and workplace relations in higher education institutions? (2) What are the sociotechnical challenges of implementing the CAS? (3) What are the advantages of the CAS in improving admissions service delivery and quality assurance in higher education institutions? The sociotechnical theoretical framework is an ideal for exploring these issues as it accommodates the understanding of dual relationship between social and technological aspects of the CAS in line with the contextual issues in its implementation. The focus of the thesis is on Tanzania's higher education institutions where the CAS is being implemented. The study is informed by data collected through interviews and documentary analysis. Data organization and analysis was done using NVivo 10 QSR software. The study demonstrates that, notwithstanding the fast development and uptake of Information and Communication Technologies (ICTs), the implementation of the CAS in Tanzania is hampered by the fact that most of the end-users of CAS (particularly applicants) have relatively low access to the ICT infrastructure. Several factors continue to have a significant effect on the implementation of CAS, which in turn lead to implications for the uptake of improved admissions service delivery and quality assurance. A digital divide, resistance to change by some higher education institutions (HEIs), poor ICT skills among applicants, the costs of internet services, unreliable electricity supply, and inadequate IT experts continue to frustrate the objective of improved admissions service delivery and quality assurance. As a technological innovation in the workplace, the CAS has led to a restructuring of admissions work tasks among admissions officers, a need to review job descriptions, introduced tighter controls over admission work processes, and has shaped admission workers' professional identities and self-presentations.
Keywords: Universities and colleges -- Tanzania -- Admission; Universities and colleges -- Tanzania -- Entrance requirements; Education, Higher -- Tanzania; Information technology -- Social aspects -- Tanzania.